Anisotropic Transport and Magnetic Properties of Charge-Density-Wave Materials RSeTe2 (R = La, Ce, Pr, Nd)*Supported by the National Basic Research Program of China under Grant No 2015CB921303, and the Strategic Priority Research Program (B) of Chinese Academy of Sciences under Grant No XDB07020100. (August 2015) - Wang, Pei-Pei; Long, Yu-Jia; Zhao, Ling-Xiao; Chen, Dong; Xue, Mian-Qi; Chen, Gen-Fu
<x content-type="archive" xml:space="preserve">Abstract</x> Single crystals of RSeTe2 (R = La, Ce, Pr, Nd) are synthesized using LiCl/RbCl flux. Transport and magnetic properties in the directions parallel and perpendicular to the a–c plane are investigated. We find that the resistivity anisotropy ρ⊥/ρ‖ lies in the range 486–615 for different compounds at 2 K, indicating the highly two-dimensional character. In both the orientations, the charge-density-wave transitions start near TCDW = 284(3) K, 316(3) K, 359(3) K for NdSeTe2, PrSeTe2, CeSeTe2, respectively, with a considerable increase in dc resistivity. While for LaSeTe2, no obvious resistivity anomaly is observed up to 380 K. The value of TCDW increases monotonically with the increasing lattice parameters. Below TCDW, slight anomalies can be observed in NdSeTe2, PrSeTe2 and CeSeTe2 with onset temperature at 193(3) K, 161(3) K, 108(3) K, respectively, decreasing as lattice parameters increase. Magnetic susceptibility measurements show that the valence state of rare earth ions are trivalence in these compounds. Antiferromagnetic-type magnetic order is formed in CeSeTe2 at 2.1 K, while no magnetic transition is observed in PrSeTe2 and NdSeTe2 down to 1.8 K.